Examining the after-school study burden of Chinese secondary school students following burden reduction policies: a sociological analysis - Yunfang Ran; Xi Wu; Yitao Wang; Zhiying Zhou; Yuan Yin (BMC Psychology)
Abstract Background To address the significant issue of students’ heavy after-school study burden, many countries have enacted relevant policies. However, the effects of policy implementation are not always desirable. This study is informed by an analysis of how dominant social imaginaries and discourses in China—emphasizing accountability, performativity, competitiveness, and capital accrual—contribute to students’ burdens. Methods This case study investigated the after-school study burden of Chinese junior secondary school students following the implementation of burden reduction policies. It involved one-on-one semi-structured interviews with 15 students, 9 parents, and 3 teachers and informal individual or group discussions. Furthermore, the researchers spent nearly three months immersing themselves in the research site, during which period they observed students’ learning status and extracurricular activities. They also reviewed assignments, learning and school extracurricular records, and teachers’ reflexive journals. Findings This study found that burden reduction policies have brought some relief to student participants due to tailored assignments, learning support, and diversified after-school programs, although the pressure remained high. The convergence of the pragmatic social imaginary and discourses in China, along with social class dispositions, strongly intervened in the humanistic aims and practices under these policies. Student participants from families of different social classes continued to face heavy after-school study burdens, such as school assignments, private tutoring, and additional exercises, and suffered from emotional stress in their pursuit of better test performance and competitiveness, without breaks in or out of school. Compared to students from higher social class families, student participants from lower social class families focused more on thin exam-oriented learning goals and required more support due to a lack of access to various after-school resources. Conclusion The study suggests that all stakeholders (policymakers, school administrators, teachers, parents, and students) collaborate in pursuing humanistic objectives in education, rather than being narrowly governed by the pragmatic social imaginary and related discourses. These stakeholders must engage in meaningful conversations and work together to create a humanistic educational environment, aiming to reduce after-school workload from school and other sources, and promote students’ pressure relief, learning and well-being based on their individual interests, learning progress, and needs.